Measuring Efficiency of the Indonesian Islamic Banks - Effendi, Yuventus (Jurnal Kajian Ekonomi dan Keuangan, 2016)
In recent years, the number of Islamic Commercial Bank and Business Unit increases significantly. Nevertheless, net profit of these banks decreased significantly in 2014. On the other hand, the Islamic Rural Banks which have slower growth of bank networks are able to manage insignificant profit reduction. Therefore, this study aims to estimate the level of inefficiency for both the Islamic Commercial banks and Islamic Rural Banks. Moreover, this study also estimates the determinants of inefficiency at the Islamic banks. There are two main contributions of this study: this study differentiates the Islamic banks into two categories and identifies causes of inefficiency. The methodology which is utilised in this study is the Stochastic Frontier Analysis based on monthly data in period 2009-2014. There are several main findings of this study. Firstly, the depositor's fund has an important role in determining the ability of financing for both types of bank. Secondly, regarding of inefficiency, the Islamic Rural Banks always efficient in the period of observation in this study, while the Islamic Commercial Banks have a lower level of efficiency relatively. Thirdly, increasing ROA which has negative and statistically significant estimated parameter is important to reduce inefficiency in the Islamic Commercial Banks.